Chemical and mechanical properties of anodized cp-titanium in NH4 H2PO4/NH4F media for biomedical applications - Games, Lucas Aloia (2012)
Potentiostatic anodizing of commercially pure titanium, using ammonium phosphate and ammonium fluoride solution as electrolyte is studied. The objective is to generate titanium oxides on the surface and phosphor compounds presenting good protective and mechanical properties, and proper adhesion to the metal substrate to remain during surgical orthopedic procedures (implants). Two different applied potentials were used to obtain different surface oxides morphologies (20 and 30V). The characterization and quantification of the generated deposits is presented as a starting point for the future application of these composite types of materials. X-ray Photoelectron Spectroscopy (XPS) and Raman spectroscopy techniques showed the presence of phosphor compounds and anatase (TiO2) as the main constitutive phases. Anodized samples presented less passivity current density with respect to the bare substrate, showing that the film formed by anodizing acts as an effective barrier to the electrolyte entrance to reach the metallic surface. Besides, mechanical properties of bare substrate were improved with the formation of anodic films: hardness value was increased in the oxide zones and the Young’s elastic modulus was decreased in the phosphor-compounds zones in the sample anodized with 30V, generating an interface with different elastic properties that could be able to enhance the prosthesis performance. Nano-scratch tests showed a very ductile behavior and good adhesion of anodic films, without any apparent signs of cracks or delamination.